Reaksi Investor terhadap Corporate Sustainability Performance: A Review Of Literature Using Stakeholder Theory - Iznillah, Muhammad Luthfi; Saidi, Julita; Rasuli, M; Nasrizal, Nasrizal (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
Climate change and sustainability have become critical global issues, prompting companies to enhance their Corporate Sustainability Performance (CSP). However, many companies have yet to optimally integrate CSP into their business strategies, which can influence investors' decision-making. This study aims to explore investors' perspectives on CSP through the lens of stakeholder theory and analyze how these perceptions affect investment decisions. A literature review approach was used to summarize and analyze relevant literature on CSP and stakeholder theory from various national and international journals. The findings indicate that investors highly value high CSP and use sustainability reports as tools for evaluating risks and opportunities. Good CSP can enhance a company's reputation, add value, and provide a competitive advantage. Despite increasing awareness of the importance of sustainability, many companies still fail to fully integrate CSP into their business strategies. This study emphasizes the importance of integrating CSP into business strategies to meet stakeholder expectations and achieve sustainable long-term performance. The theoretical and managerial implications of this research highlight the importance of transparency and accountability in sustainability reporting to enhance investor trust. The limitations of this study include the use of secondary data and a literature review approach. Future research is recommended to employ empirical methods with primary data collection to gain deeper insights.